Sharps injuries and splash exposures among healthcare workers in the United Arab Emirates - Karkaz, Ibtisam; Abdullahi, Aminu; Alblooshi, Khadeeja; Elbarazi, Iffat; Grivna, Michal; Sheek-Hussein, Mohamud; Ádám, Balázs (Frontiers in Public Health, 2025)
BackgroundThe present study aimed to estimate the rate of sharps injuries and splash exposures among healthcare workers in the United Arab Emirates (UAE) government hospitals and to determine the risk factors associated with these incidents of possible severe consequences.MethodsA cross-sectional study was carried out among healthcare workers employed in government hospitals in the Abu Dhabi Emirate of the UAE. An online survey was distributed to estimate incidents of sharps injuries and splash exposures between 2019 and 2021. The study explored characteristics, risk factors, consequences, and preventive measures in response to these incidents.ResultsIn the current study, 820 healthcare workers responded to the invitation, and 678 completed the questionnaire. Among the participants, 14.6% suffered sharp injuries or splash exposures in the study period, but only 70% reported the incident. Dealing with uncooperative or restless patients and workplace pressure were the two most frequent contributing factors, while suturing and manipulating needles in patients were the most common circumstances leading to these incidents. Most healthcare workers said their institutions had rules for the control of sharps injuries and splash exposures, and the majority thought the supplied personal protective equipment was sufficient to prevent the incidents and their serious complications; nevertheless, almost 30% of them never used auto-retractable needles.ConclusionSharps injuries and splash exposures are still frequent among healthcare workers in the UAE; therefore, interventions encouraging reporting and focusing on training for safe practices, ensuring adequate personal protective equipment supply, including safety-engineered products like auto-retractable needles, are recommended to mitigate the risk.